2017
DOI: 10.1002/nvsm.1573
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cause‐related marketing for differential positioning of market entrant in developing market: An exploratory study in Indian context

Abstract: Cause‐related marketing is being increasingly used for forging strong relation between the brand and the customer. It is primarily being used by the well‐established brands to further strengthen their position in the market as it leads to a positive image of the brand, and customers are more receptive towards such brands because they tend to provide them with tangible as well as intangible benefits. This study tends to identify the effectiveness of cause‐related marketing as a marketing tool for newly launched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…The study reveals that the fit between an organization's products/services with the cause supported can build a positive attitude toward the cause, but may not influence the purchase decision. This finding is consistent with the results of Shree et al ( 2017), who found that Indian consumers were supportive of CRM, but failed to reveal if the support translated to any actual purchases, while a study done in Pakistan affirmed that consumers failed to recollect the brand, even when they were positive about the initiatives (Shabbir et al, 2010). This indicates that consumers in developing nations still place importance on the conventional purchase factors in their decision making, while CSR / CRM are factors that can affect the consumer's attitude, which in turn can act as a savior during negative publicity.…”
Section: Practical Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…The study reveals that the fit between an organization's products/services with the cause supported can build a positive attitude toward the cause, but may not influence the purchase decision. This finding is consistent with the results of Shree et al ( 2017), who found that Indian consumers were supportive of CRM, but failed to reveal if the support translated to any actual purchases, while a study done in Pakistan affirmed that consumers failed to recollect the brand, even when they were positive about the initiatives (Shabbir et al, 2010). This indicates that consumers in developing nations still place importance on the conventional purchase factors in their decision making, while CSR / CRM are factors that can affect the consumer's attitude, which in turn can act as a savior during negative publicity.…”
Section: Practical Implicationssupporting
confidence: 85%
“…Even the past literature provides evidence that CRM has reached the mature stage in the American and European markets (Webb & Mohr, 1998) and significant studies have been conducted (Hou et al, 2008) in those developed economies; while very little research has been conducted on the application of CRM as a tool for marketing in developing economies (Shree et al, 2017). Even though CRM has been rapidly growing in the Asian region, there is still a dearth of research (Chattananon et al, 2008;Shabbir et al, 2010;Subrahmanyan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cause marketing has been found to be an effective element in the marketing process as a means of adding value to the product (Wymer & Samu, ). It has also proven effective in a developing country when linking new food products with important values (Shree, Gupta, & Sagar, ).…”
Section: Discussionmentioning
confidence: 99%
“…To seek a profile of BoP consumer markets that accounts for general BoP generalizations and country-specific consumer phenomena, an exploratory design was used. This approach is aligned to studies where there is little prior knowledge on which to build either descriptive or causal research (Alam, 2002; Harrison and Reilly, 2011; Cairns et al , 2016; Rancati et al , 2016; Shree et al , 2017). Other BoP studies have used exploratory designs for the comparable reason of a lack of sufficient theoretical framework for the phenomenon of interest (London and Hart, 2004; Barki and Parente, 2006).…”
Section: Profiling Global and Local Bottom-of-the-pyramid Consumer Characteristics: The Case Of South Africamentioning
confidence: 99%